Worldwide trends in volume and quality of published protocols of randomized controlled trials. - Belle V van Rosmalen; Ingo Alldinger; Kasia P Cieslak; Roos Wennink; Mike Clarke; Usama Ahmed Ali; Marc G H Besselink (PLoS ONE)
Introduction Publishing protocols of randomized controlled trials (RCT) facilitates a more detailed description of study rational, design, and related ethical and safety issues, which should promote transparency. Little is known about how the practice of publishing protocols developed over time. Therefore, this study describes the worldwide trends in volume and methodological quality of published RCT protocols. Methods A systematic search was performed in PubMed and EMBASE, identifying RCT protocols published over a decade from 1 September 2001. Data were extracted on quality characteristics of RCT protocols. The primary outcome, methodological quality, was assessed by individual methodological characteristics (adequate generation of allocation, concealment of allocation and intention-to-treat analysis). A comparison was made by publication period (First, September 2001- December 2004; Second, January 2005-May 2008; Third, June 2008-September 2011), geographical region and medical specialty. Results The number of published RCT protocols increased from 69 in the first, to 390 in the third period (p<0.0001). Internal medicine and paediatrics were the most common specialty topics. Whereas most published RCT protocols in the first period originated from North America (n = 30, 44%), in the second and third period this was Europe (respectively, n = 65, 47% and n = 190, 48%, p = 0.02). Quality of RCT protocols was higher in Europe and Australasia, compared to North America (OR = 0.63, CI = 0.40-0.99, p = 0.04). Adequate generation of allocation improved with time (44%, 58%, 67%, p = 0.001), as did concealment of allocation (38%, 53%, 55%, p = 0.03). Surgical protocols had the highest quality among the three specialty topics used in this study (OR = 1.94, CI = 1.09-3.45, p = 0.02). Conclusion Publishing RCT protocols has become popular, with a five-fold increase in the past decade. The quality of published RCT protocols also improved, although variation between geographical regions and across medical specialties was seen. This emphasizes the importance of international standards of comprehensive training in RCT methodology.